Physical reality of the Preisach model for organic ferroelectrics - Urbanavičiūtė, Indrė; Cornelissen, Tim D.; Meng, Xiao; Sijbesma, Rint P.; Kemerink, Martijn (Nature Communications, 2018)
Though the Preisach model successfully describes hysteretic switching in ferroelectrics, the physical reality of the model remains elusive. Here, the authors explained the origin of the experimental Preisach distribution and its effect on switching kinetics and materials’ potential applications